Studies in Catullan verse : An analysis of word types and patterns in the Polymetra - Loomis, Julia W. (Mnemosyne, Supplements, 1972)
Chronicles the French revolution, from the gathering of the Estates-General, after one-hundred-twenty-five years of silence, to disunity within the Committee of Public Safety, The fall of Robespierre, and the end of the Reign of Terror.